2008
DOI: 10.21273/hortsci.43.3.667
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Hazelnut (Corylus avellana L.) Germplasm in Northeastern Spain

Abstract: In Spain, hazelnut is mainly cultivated in Catalonia, a region in the northeast. The province of Tarragona accounts for 88% of the total Spanish area planted to hazelnut. Almost 80% of the production in Tarragona is of the local cultivar Negret, with others cultivated to a lesser extent. Minor cultivars are only sporadically present in older orchards, farm yards and gardens, and have been collected for preservation. In this work, 16 SSR markers were used to fingerprint 18 minor hazelnut cultivars from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 20 publications
3
31
0
Order By: Relevance
“…Trueness-to-type of the accessions was previously verified by Boccacci et al (2005Boccacci et al ( , 2008 and Ghanbari et al (2005) using nSSR markers. The cultivars were assigned to four groups on the basis of their country of origin (Table 1).…”
Section: Plant Materials and Dna Extractionmentioning
confidence: 77%
See 1 more Smart Citation
“…Trueness-to-type of the accessions was previously verified by Boccacci et al (2005Boccacci et al ( , 2008 and Ghanbari et al (2005) using nSSR markers. The cultivars were assigned to four groups on the basis of their country of origin (Table 1).…”
Section: Plant Materials and Dna Extractionmentioning
confidence: 77%
“…nSSR loci have been used to fingerprint and to identify mistakes in hazelnut accessions from several germplasm repositories Gökirmak et al 2008). These studies investigated genetic relationships among cultivars grown in important production areas, identified accessions with identical fingerprints, and suggested the parentage for several cultivars (Boccacci et al 2006(Boccacci et al , 2008Ghanbari et al 2005;Gökirmak et al 2008). In particular, Boccacci et al (2006) and Gökirmak et al (2008) concluded that cultivars from Italy and Spain are genetically related.…”
Section: Introductionmentioning
confidence: 99%
“…2005). In Europe, 16 SSR loci were used to fingerprint 78 cultivars in Italy and 18 minor cultivars in Spain (Boccacci et al. 2006, 2008).…”
mentioning
confidence: 99%
“…Hazelnut is monoecious, dichogamous, wind pollinated and has sporophytic incompatibility controlled by a single S‐locus with multiple alleles (Thompson 1979, Mehlenbacher 1997). European hazelnut shows a high level of phenotypic diversity and numerous cultivars have been described based on their nut and husk phenotypes (Alvarez Requejo 1965, Tasias Valls 1975, Boccacci et al. 2008).…”
mentioning
confidence: 99%
“…2006). SSR markers were used to analyse genetic relationships among cultivars (Boccacci et al. 2006, 2008, Gökirmak et al.…”
mentioning
confidence: 99%